Common goals and differential commitments: the role of emerging economies in global development - Neissan Alessandro Besharati (Deutsches Institut für Entwicklungspolitik (DIE), 2013)
The following discussion paper explores the heated debate around `common goals and differential commitments' in international development cooperation. It tries to capture the views and positions of the so-called `emerging economies' on their role and contribution to global development and the post-2015 agenda. It explains the divergence between North-South and South-South cooperation with regard to their historical narratives, conceptual paradigms, delivery approaches, functions and capacity. It highlights the importance of standard-setting, monitoring, accountability and peer-review but it also explains the technical challenges and political tensions in bringing the `Southern providers' into the regimes and systems led by the OECD-DAC and the current post-Busan Global Partnership. The paper explains the challenges of categorising the new development partners, and defining and measuring the quantum, quality and effectiveness of their development cooperation activities. It stresses the importance of developing a framework for monitoring and evaluating South-South cooperation and the identification of appropriate institutional platforms for such discussions to take place. The paper is based on empirical research and engagement with numerous Southern stakeholders and offers concrete policy proposals for the different development partners involved in the debate.
Keywords: 330; Aufstrebende Mächte; Wirksamkeit und Evaluierung